Smoking cessation advice: Knowledge, attitude, and practice among clinical dental students' - Allama Prabhu; Jayesh Kumar Jain; B Sakeenabhi; P G Naveen Kumar; Mohamed Imranulla; Mallikarjuna Ragher (Wolters Kluwer Medknow Publications, 2017)
Background: Smoking is the single most important public health challenge facing the National Health Service. The detrimental effects on the general health of tobacco smoking are well documented. Smoking is a primary risk factor for oral cancer and many oral diseases. Dental professional scan plays an important role in preventing adverse health effects by promoting smoking cessation. Objective: To assess the knowledge, attitude, and practice among clinical dental students in giving smoking cessation advice and to explore the barriers to this activity. Materials and Methods: A total of 262 clinical dental trainee of two dental colleges (College of Dental Sciences and Bapuji Dental College) of Davangere city were included in the survey. A self-administered questionnaire was administered to assess the knowledge, attitude, and practice toward Tobacco Cessation Advise. Results: Among the 262 participants in the study, around 51% said they know about Nicotine Replacement Therapy, and among them, only 4.6% were aware of the options available in the market. When asked about 5A's of tobacco cessation, only 35.5% were aware of it. Similarly, when asked about 5R's of tobacco cessation, 48.5% were unaware of it. Conclusions: The respondents did not have sufficient knowledge regarding tobacco cessation advice. With patient's disinterest and lack of time being quoted as the important barriers in providing tobacco cessation advice, it is highly recommended that there is need to incorporate few chapters on tobacco, its effect and cessation of habit in the undergraduate dental curriculum with simultaneous application of the same in clinical practice.